2010
DOI: 10.1186/1824-7288-36-66
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between severe obesity and gut inflammation in children: what's next?

Abstract: BackgroundPreliminary evidence suggests an association between obesity and gut inflammation.AimsTo evaluate the frequency of glucose abnormalities and their correlation with systemic and intestinal inflammation in severely obese children.Patients and MethodsThirty-four children (25 males; median age 10.8 ± 3.4 yrs) with severe obesity (BMI >95%) were screened for diabetes with oral glucose tolerance test (OGTT), systemic inflammation with C-reactive protein (CRP) and gut inflammation with rectal nitric oxide (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 30 publications
0
31
0
1
Order By: Relevance
“…Inflammation causes endothelial dysfunction that may contribute to increased systemic vascular resistance and lead to the development of hypertension. Moreover, we did not find an association between calprotectin and hypertension, and thus whether inflammation is a cause or effect of hypertension is something that is not yet well understood [33,34].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Inflammation causes endothelial dysfunction that may contribute to increased systemic vascular resistance and lead to the development of hypertension. Moreover, we did not find an association between calprotectin and hypertension, and thus whether inflammation is a cause or effect of hypertension is something that is not yet well understood [33,34].…”
Section: Discussionmentioning
confidence: 71%
“…Of importance is the fact that we reported a positive correlation between increased serum calprotectin and pathological FBG and insulin resistance in obese children despite the absence of specific intestinal symptoms and of intestinal disorders, confirming a key role of proinflammatory factors in insulin-resistance pathogenesis and supporting the evolving concept that inflammation might be a common denominator linking obesity to many of its pathological sequelae, through the increased expression of some inflammatory cytokines and several signaling pathways activation, interfering with insulin signaling and action [33][34][35].…”
Section: Discussionmentioning
confidence: 82%
“…In line with these functions, phagocytes reportedly express S100A8 and S100A9 under multiple inflammatory conditions, i.e., inflammatory bowel disease, rheumatoid arthritis or allograft rejection (8)(9)(10), whereas numerous pathological conditions associated with inflammation in humans are associated with elevated S100A8 and S100A9 levels (11). Furthermore, the inflammatory factors interleukin (IL)-1, interferon (IFN)-γ and tumor necrosis factor (TNF)-α induce the expression and secretion of the S100A8/A9 heterodimer (12)(13)(14).…”
mentioning
confidence: 92%
“…In a recent study, the levels of pro-inflammatory cytokines and endotoxinrelated parameters were shown to increase in patients with NAFLD, and pro-inflammatory cytokine levels were correlated with the histological severity of NAFLD (18). Fecal calprotectin levels were studied in obese children, and a correlation was found with BMI and abnormal oral glucose tolerance test in children (19).…”
Section: Discussionmentioning
confidence: 99%